Dupla cidadania: ítalo-brasilianidade como valorização e afirmação étnica no Sul do Brasil - Costa, Jamile dos Santos Pereira (2017)
This study presents questionings that resulted from an ethnographic study which was carried out in the years between 2015-2017. The reflections of this master thesis sought to answer the following research question: Would the process of legal recognition of Italian citizenship be arousing feelings of belonging and identification with Italians and Italian-Brazilians in descendants of Italian immigrants in Brazil? Therefore, this is an ethnographic study carried out among descendants of Italian immigrants who had completed their legal processes of recognition of their Italian citizenship, which aimed at understanding the dynamics involved in these processes. The specific objectives of this study were to identify the social and cultural elements that come to be valued by these Italian-Brazilian citizens and to observe the narratives among these double citizens and their understandings of the importance of social networks (virtual and non-virtual) in the construction of a self-definition as an ethnical group. Those perceptions led us to observe that there is a valorization of affective ties with the past brought by those Italian ancestors. Also, these affective ties are revitalized today through cultural expressions; family reunions; memories of the immigration, and the process of recognition of Italian citizenship. This process is not only a result of a political right, but it is also an ethnical marker of the diversity of this group on Brazilian soil. Moreover, it forms an agency and an Italian-Brazilian identity that guarantees social status before other ethnical groups in Brazil. The recognition of their Italian citizenship, however, does not make them Italians when they are in foreign lands.